Analisis Korelasi antara Kemampuan Pemecahan Masalah dan Miskonsepsi pada Materi Fluida Statis - Aurriel Magita Arsha Dittya; Nur Endah Susilowati; Duden Saepuzaman; Erni Ernawati (Mataram University, 2026)
Misconceptions in physics learning can hinder students conceptual understanding and affect their ability to solve problems effectively. Therefore, investigating the relationship between misconceptions and problem-solving ability is important to provide information for improving physics learning, particularly in static fluid concepts. This study aims to analyze the correlation between students’ problem-solving ability and misconceptions in static fluid material. The study employed a quantitative correlational design involving 31 students of class XI MIPA at a senior high school in Bandung. The sampling technique used was total sampling. Data were collected using a misconception test consisting of 10 two-tier multiple-choice questions and a problem-solving ability test consisting of 10 essay questions. Data analysis was conducted using the Kolmogorov-Smirnov normality test and Spearman’s rho correlation test. The normality test results indicated that both misconception and problem-solving ability data were not normally distributed (p < 0.05). Therefore, the Spearman correlation test was employed. The results showed a correlation coefficient of 0.291 with a significance value of 0.090 (p > 0.05). These findings indicate that there is a positive but statistically insignificant correlation between misconceptions and problem-solving ability. The correlation level is categorized as weak. Therefore, misconceptions do not significantly affect students’ problem-solving ability in static fluid material.